2018
DOI: 10.1109/tit.2017.2785237
|View full text |Cite
|
Sign up to set email alerts
|

The Exact Rate-Memory Tradeoff for Caching With Uncoded Prefetching

Abstract: Abstract-We consider a basic cache network, in which a single server is connected to multiple users via a shared bottleneck link. The server has a database of files (content). Each user has an isolated memory that can be used to cache content in a prefetching phase. In a following delivery phase, each user requests a file from the database, and the server needs to deliver users' demands as efficiently as possible by taking into account their cache contents. We focus on an important and commonly used class of p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
285
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 305 publications
(288 citation statements)
references
References 53 publications
2
285
0
1
Order By: Relevance
“…Our novel IC bound achieves our novel converse A generalized version of the scheme in [13] from the viewpoint of index coding knowledge, the best random coding achievable bound for the general IC problem to date. We then show that our novel IC scheme matches our converse bound for centralized cache-aided systems with uncoded cache placement when there are less files than users, and attains the same load as the scheme in [26].…”
Section: Cachingmentioning
confidence: 76%
See 4 more Smart Citations
“…Our novel IC bound achieves our novel converse A generalized version of the scheme in [13] from the viewpoint of index coding knowledge, the best random coding achievable bound for the general IC problem to date. We then show that our novel IC scheme matches our converse bound for centralized cache-aided systems with uncoded cache placement when there are less files than users, and attains the same load as the scheme in [26].…”
Section: Cachingmentioning
confidence: 76%
“…In [1], Maddah-Ali and Niesen analytically showed that the load of their proposed scheme is to within a factor of 12 of a cut-set-type converse bound, but it was noted in [11] that it numerically appeared to be optimal to within a factor 4.7. The scheme in [1] has been improved in many ways; examples of schemes with uncoded cache placement are [4], [5], [12], [13], while with coded cache placement are [14]- [18].…”
Section: A Past Workmentioning
confidence: 99%
See 3 more Smart Citations